La traite et la production laitiere dans les troupeaux villageois sedentaires au nord de la Cote-d'Ivoire - Godet, G.; Landais, E.; Poivey, J.P.; Agabriel, J.; Mawudo, W. (1981)
Describes milking practices and milk production of village herds in Ivory Coast. Milking was practiced regularly in more than 75 percent of the sedentary herds in the area. Quantities of milk produced varied depending on season: 600 to 900 ml of milk per female per day in the N'Dama breed, 400 to 600 ml in the Baoule breed, which amounts to 30 to 40 percent of the total daily production of the females. Economic evaluations on the effects of milking on calves performance, beef production, female fertility; and overall return to herdsmen included.